Uslūb al-Iltifāt fī al-Juzʾ al-Akhīr min al-Qurʾān al-Karīm - Aqdi Rofiq Asnawi (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
Iltifāt is one of the most important rhetorical devices in the Arabic language and one of the most frequently used stylistic features in the Holy Qur'an. It has been described as the